Enhancing oxygen reduction reaction activity of perovskite oxides cathode for solid oxide fuel cells using a novel anion doping strategy - Liu, Y.; Meng, X.; Yu, F.; Yin, M.; Yang, N.; Meng, B.; Sofianos, Veronica; Liu, Shaomin (Elsevier Ltd, 2018)
Possessing a high oxygen reduction reaction (ORR) activity is one of the most important prerequisites for the cathode to ensure an efficient solid oxide fuel cell. Herein, a highly active cathode is developed by doping the fluorine anion in anion sites of perovskite oxides (ABO3). The electrocatalytic activities of three different cathode samples including the original perovskite La0.6Sr0.4Co0.2Fe0.8O3-d(LSCF), the doped La0.6Sr0.4Co0.2Fe0.8O2.95-dF0.05(LSCFF0.05) and La0.6Sr0.4Co0.2Fe0.8O2.9-dF0.1(LSCFF0.1) are comparatively investigated. The fluorine doped perovskites reveal higher electrochemical performance than the original perovskite. Based on three cathodes of LSCF, LSCFF0.05 and LSCFF0.1 operated at 850 °C, the measured area specific resistance was 0.018, 0.017 and 0.91 O cm2, respectively; and the respective maximum power density of the single fuel cell using the 9-µm-thick YSZ electrolyte was 754, 1005, and 737 mW cm-2. Such performance results vividly indicate that, the obtained perovskite oxyfluoride by doping an optimum amount of F ions can efficiently improve ORR activity and thus is a feasible strategy to develop cathode for high-performance solid oxide fuel cells.